Asimetri Informasi Memoderasi Akuntansi Hijau dan Kualitas Pengungkapan Lingkungan dan Sosial terhadap Volatilitas Harga Saham - Margaretha Jessica Wijaya; Nera Marinda Machdar (UNIVERSITAS KALBIS, 2022)
This research was aimed to know the influences of green accounting and quality of environmental and social disclosure on stock price volatility with asymmetry information as a moderator. Stock price volatility is the movement of stock price that goes up and down on stock exchange. In this study, the sample that used are the listed mining companies of Indonesia Stock Exchange in 2013-2018 with 46 population companies. With purposive sampling, this research got 18 mining companies as sample. This research used panel data regression method with common effect approach model. The results of this research are green accounting has positive influence on stock price volatility, and quality of environmental and social disclosure has positive influence on stock price volatility. Asymmetry information as moderating variable cannot strengthen the influence of green accounting on stock price volatility, and the influence of quality of environmental and social disclosure on stock price volatility.